Experimental design and performance evaluation of a solar panel-based visible light communication system for greenhouse applications - Soto, I (NATURE PORTFOLIO, 2025)
This paper presents the design, implementation, and experimental evaluation of a visible light communication (VLC) system using a small solar panel with a custom signal-conditioning circuit as an optical receiver in a greenhouse environment. In this context, VLC can enables simultaneous lighting and data transmission, while solar panels can serve dual roles as energy harvesters and receivers. The work focuses on using mini solar panels, coupled with tailored circuitry, to address practical challenges in greenhouse communication. Theoretical modeling includes Lambertian emission and Beer-Lambert attenuation to characterize the optical channel, while accounting for the solar panel s inherent low-pass filtering, which limits frequency response. Key performance metrics, including received optical power, bit error ratio (BER), and communication range, were evaluated under varying humidity conditions and at different transmitter-receiver distances. Experimental results using a modulated LED source showed that under high-humidity greenhouse conditions, the system achieves BER \documentclass[12pt]{minimal} \usepackage{amsmath} \usepackage{wasysym} \usepackage{amsfonts} \usepackage{amssymb} \usepackage{amsbsy} \usepackage{mathrsfs} \usepackage{upgreek} \setlength{\oddsidemargin}{-69pt} \begin{document}$$\approx 10<^>{-3}$$\end{document} only at short ranges (\documentclass[12pt]{minimal} \usepackage{amsmath} \usepackage{wasysym} \usepackage{amsfonts} \usepackage{amssymb} \usepackage{amsbsy} \usepackage{mathrsfs} \usepackage{upgreek} \setlength{\oddsidemargin}{-69pt} \begin{document}$$\approx$$\end{document} 0.3-0.4 m), increasing to \documentclass[12pt]{minimal} \usepackage{amsmath} \usepackage{wasysym} \usepackage{amsfonts} \usepackage{amssymb} \usepackage{amsbsy} \usepackage{mathrsfs} \usepackage{upgreek} \setlength{\oddsidemargin}{-69pt} \begin{document}$$10<^>{-2}$$\end{document}-\documentclass[12pt]{minimal} \usepackage{amsmath} \usepackage{wasysym} \usepackage{amsfonts} \usepackage{amssymb} \usepackage{amsbsy} \usepackage{mathrsfs} \usepackage{upgreek} \setlength{\oddsidemargin}{-69pt} \begin{document}$$10<^>{-1}$$\end{document} for 0.55-0.70 m. Beyond this range, link performance degrades due to receiver sensitivity limits. For reference, comparisons with reported photodetector results under similar greenhouse conditions highlighted that solar panels, while less sensitive at long distances, remain a viable option for robust, low-data-rate VLC applications. These findings offer insights into the design of photovoltaic-based VLC systems, highlighting opportunities to enhance receiver sensitivity and optimize dual-purpose operation.